2013
DOI: 10.1111/jre.12065
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide of Aggregatibacter actinomycetemcomitans up‐regulates inflammatory cytokines, prostaglandin E2 synthesis and osteoclast formation in interleukin‐1 receptor antagonist‐deficient mice

Abstract: IL-1Ra regulates IL-1 activity and appears to reduce the levels of other inflammatory cytokines, including TNF-α and IL-6, while it also reduces expression of the EP4 receptor related to prostanoid sensitivity and osteoclast formation. These results suggest that IL-1Ra is an important molecule for inhibition of inflammatory periodontal bone resorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
39
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 46 publications
0
39
0
2
Order By: Relevance
“…Histo- pathological analysis has revealed marked synovial and periarticular inflammation, accompanied by articular erosion, caused by invasion of granulation tissue in those mice (25,52). Mizutani et al reported that stimulation of supernatant fluids from IL-1Ra KO mouse peritoneal macrophages with A. actinomycetemcomitans LPS induced severe calvarial bone resorption, in contrast to the findings for WT mice (22). Accordingly, we reasoned that IL-1Ra KO mice might be a suitable model animal for studies of experimental periodontitis.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Histo- pathological analysis has revealed marked synovial and periarticular inflammation, accompanied by articular erosion, caused by invasion of granulation tissue in those mice (25,52). Mizutani et al reported that stimulation of supernatant fluids from IL-1Ra KO mouse peritoneal macrophages with A. actinomycetemcomitans LPS induced severe calvarial bone resorption, in contrast to the findings for WT mice (22). Accordingly, we reasoned that IL-1Ra KO mice might be a suitable model animal for studies of experimental periodontitis.…”
Section: Discussionmentioning
confidence: 85%
“…RANK is expressed at very high levels on osteoclast precursors and is required for osteoclast differentiation and activation (55). RANK mRNA expression is elevated in IL-1Ra KO mouse bone marrow cells (22). RANKL binds to RANK, to induce bone resorption (56,57).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data and previous study showed that LPS could trigger osteoclast precursor RAW264.7 cells to release pro-inflammatory cytokines TNF-α, IL-1β and PGE 2 , that directly stimulate osteoclast differentiation, and increase excessive bone resorption. 4,5) Furthermore, we demonstrated that LPS dramatically increased mRNA expression of osteoclast-specific genes such as TRAP, cathepsin K and MMP-9 (Table 3), involved in degrading the bone matrix during bone resorption by initiating the bone resorptive process, or by removing the collageous layer from the bone surface before demineralization begins. Combining these previous reports and our results, we conclude that LPS can directly induce osteoclastogenesis independent of RANKL, and afterwards cause bone resorption in inflammatory bone destruction diseases like osteomyelitis, septic arthritis, periodontitis.…”
Section: Discussionmentioning
confidence: 88%
“…3) LPS induces the production of pro-inflammatory cytokines such as tumor necrosis factor (TNF)-α, interleukin (IL)-1β, prostaglandin E 2 (PGE 2 ) and IL-6, that are able to directly stimulate osteoclast differentiation and ultimately lead to the destructive bone loss via increasing the expression of receptor activator for nuclear factor-κB ligand (RANKL). [4][5][6] RANKL is the key cytokine that stimulates entire processes for the development of bone-resorbing osteoclasts. 5,7) The binding of RANKL to its receptor RANK triggers the activation of signaling molecules such as Akt that subsequently induce the activation of transcription factors to regulate the expression of genes required for osteoclast differentiation and survival.…”
mentioning
confidence: 99%